Analisis Perbedaan Abnormal Return dan Kinerja Keuangan Perusahaan Sebelum dan Sesudah Merger atau Akuisisi - Steffi Aprilda Natasya Lim; Suhajar Wiyoto (Ultima Accounting : Jurnal Ilmu Akuntansi, 2014)
The objective of this research is to examine the difference of abnormal return, and companies’ financial performance, before and after merger or acquisition. The companies’ financial performances are projected by financial ratios, which are return on asset and return on equity. This research is expected to help economic actors in making economic decisions related to merger and acquisition. The samples in this study are 11 companies that listed in Indonesia Stock Exchange (Bursa Efek Indonesia) in the year 2010-2011, except financial sectors and done corporate action merger or acquisition. The sample in this study determined based on purposive sampling. Data used in this study is secondary data such as annual reports or financial reports. The results from this study are (1) there is no difference of abnormal return before and after merger or acquisition (2) there is no difference of companies’ financial performance that projected by return on asset before and after merger or acquisition (3) there is a difference of companies’ financial performance that projected by return on equity before and after merger or acquisition. Keywords: abnormal return, return on asset, return on equity, merger, acquisition